The importance of studying inter-regional spillover effects of European policies: Application of the RHOMOLO model for Poland - Patrizio Lecca; Simone Salotti; Andrea Conte (European Commission, Joint Research Centre (JRC), 2020)
The European cohesion policy is the EU's main investment policy and targets all regions and cities across the EU to support job creation, business competitiveness, economic growth, and sustainable development. In the 2014-2020 programming period, one third of the EU budget has been allocated to the projects under this policy. This report contains a macroeconomic impact assessment of the European cohesion policy with a focus on Polish regions. The analysis deals in particular with the spillover effects arising from the policy intervention resulting from indirect trade effects and other inter-regional interdependencies and interactions. The analysis shows that the policy has a positive long-run impact, lasting years after the end of the programmes. This reflects the fact that cohesion policy supports investments in key engines of growth improving the structure of the Polish economy.
Keywords: C68; R13; 330; Rhomolo; region; growth; cohesion policy; Poland